Comparison of Quality of Work Life and Job Satisfaction of Midwives Working in Related and Unrelated workplaces to Midwifery - Mahdieh Hardani; Mitra Tadayon Najafabadi; Amin Torabipour Hamedani; Tahmineh Farjokhoda; Saeed Ghanbari Chahanjiri (Mashhad University of Medical Sciences, 2023)
Background & aim: Quality of work life and job satisfaction are two important components in creating a developed and capable workforce in all health care systems. The midwifery profession needs special attention due to its feminine nature and having many job stresses. The aim of this study was to compare the quality of work life and job satisfaction of midwives working in related and non-related workplaces to midwifery in Iran.Methods: The current study was a cross-sectional study using census sampling method, which was performed on 106 midwives (53 working in related and 53 working in unrelated workplaces) in all hospitals of Yazd, Iran in 2021. Data collection tools included demographic Questionnaire (including personal and midwifery characteristics), Walton Work Life Quality and Job Satisfaction Questionnaire. Independent t-test, Mann-Whitney test, correlation coefficient, regression analysis and Chi-square were used to analyze the data.Results: According to the results, the mean total score of quality of work life in midwives working in related workplaces (80.03±12.62) was higher than the mean of overall scores of quality of working life in midwives working in unrelated workplaces (76.94±9.11). However, this difference was not statistically significant except in two dimensions of integration and social cohesion (P=0.027) as well as development of human capabilities (P=0.002). There was no significant difference in job satisfaction of two groups (P=0.242).Conclusion: The results showed that quality of work life in midwives working in related departments are higher than midwives working in unrelated workplaces. Therefore, it is recommended to use midwives as much as possible in positions and workplaces related to their field of study.